Researcher Profile: An Interview with Sarah Asebedo, Ph.D. - Martie Gillen (Journal of Financial Therapy, 2016)
Sarah Asebedo, Ph.D., CFP®, is an Assistant Professor of Personal Financial Planning with Texas Tech University. With extensive financial planning practitioner experience, her goal is to connect research and financial planning practice with a focus on the relationship between psychological attributes, financial conflicts, and financial behavior. Her work has been published in the Journal of Financial Planning, Journal of Financial Therapy, Journal of Financial Counseling and Planning, and Financial Planning Review. Asebedo currently serves as President-Elect for the Financial Therapy Association. She earned her Ph.D. in Personal Financial Planning from Kansas State University.
Keywords: financial therapy; well-being; research; Financial Therapy Association